Intimate Partner Violence Polyvictimization and Health Outcomes - Cho, Hyunkag (Violence against women, 2023)
This study examines how gender interacts with polyvictimization patterns in survivors’ health problems using 8,587 survivors of intimate partner violence from the National Intimate Partner and Sexual Violence Survey, a nationally representative sample collected in 2010. Polyvictimization included six categories that were created in our previous work: sexual violence, physical and psychological violence, coercive control, multiple violence, stalking, and psychological aggression. Multiple violence was associated with chronic pain, headache, difficulty sleeping, and poor health perception. Females experiencing coercive control were more likely to have chronic pain than males. The appropriate assessment of gendered patterns of polyvictimization, and relevant subsequent services and support will better address health problems among survivors.